SEG Technical Program Expanded Abstracts 1991 1991
DOI: 10.1190/1.1889147
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐borehole electromagnetic induction for reservoir characterization

Abstract: Audio-frequency cross-borehole electromagnetics (EM) is aninteresting alternative to existing techniques for reservoir characterization. With this method signals may be propagated several hundreds of meters &rough typical sand/shale reservoirs and data may be collected at high accuracy with a high sensitivity to thk subsurface resistivity A vertical component, cross-borehole EM field system has been designed and built by Lawrence Livermore and Lawrence Berkeley laboratories for reservoir evaluation and monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…However, the work of Zhou (1989) showed that a low frequency analog to diffraction tomography is useful in determining the orientation of fractures in a fracture zone. Wilt, et al (1991) have demonstrated that single frequency measurements can be made in oil wells separated by loom, while Wilt and Schenkel(1992) and Hanson, et al ( 1991) have shown that these type of cross well measurements are useful in monitoring environmental injection processes. In this thesis methods will be developed to both model the audio frequency EM response to conductivity changes caused by these processes, and to interpret data collected in cross-well EM surveys.…”
Section: Geophysical Methods For Reservoir Process Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the work of Zhou (1989) showed that a low frequency analog to diffraction tomography is useful in determining the orientation of fractures in a fracture zone. Wilt, et al (1991) have demonstrated that single frequency measurements can be made in oil wells separated by loom, while Wilt and Schenkel(1992) and Hanson, et al ( 1991) have shown that these type of cross well measurements are useful in monitoring environmental injection processes. In this thesis methods will be developed to both model the audio frequency EM response to conductivity changes caused by these processes, and to interpret data collected in cross-well EM surveys.…”
Section: Geophysical Methods For Reservoir Process Monitoringmentioning
confidence: 99%
“…EOR injection processes will be simulated with forward models and the resulting conductivity images analized for accuracy. The theory for a more complicated, one dimensional layered background model will be incorporated into the imaging scheme and then applied to field data collected by Wilt, et al (1991). Finally as in the preceeding chapters we will use the 2D cylindrically symmetric imaging scheme on synthetic data generated with 3D models to determine the limitations of the simplified cylindrical geometry.…”
Section: Scope Of This Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…With these simple analog systems, we have collected high-quality data at a variety of fields at borehole separations from 10 to 300 m using frequencies from 100 Hz to 100 kHz [3]. Data is typically repeatable and reciprocal to 1 percent.…”
Section: Field Systemsmentioning
confidence: 99%